Factors associated with failure of high-flow nasal cannula oxygen therapy in patients with severe COVID-19: a retrospective case series. Issue 5 (May 2022) - Ma, Xiao-Huan; An, Meng-Meng; Yin, Fang; Zhang, Jie; Peng, Meng-Yun; Guan, Hong; Gong, Ping
Objective: To identify factors associated with high-flow nasal cannula (HFNC) therapy failure in patients with severe COVID-19. Methods: We retrospectively examined clinical and laboratory data upon admission, treatments, and outcomes of patients with severe COVID-19. Sequential Organ Failure Assessment (SOFA) scores were also calculated. Results: Of 54 patients with severe COVID-19, HFNC therapy was successful in 28 (51.9%) and unsuccessful in 26 (48.1%). HFNC therapy failure was more common in patients aged ≥60 years and in men. Compared with patients with successful HFNC therapy, patients with HFNC therapy failure had higher percentages of fatigue, anorexia, and cardiovascular disease; a longer time from symptom onset to diagnosis; higher SOFA scores; a higher body temperature, respiratory rate, and heart rate; more complications, including acute respiratory distress syndrome, septic shock, myocardial damage, and acute kidney injury; a higher C-reactive protein concentration, neutrophil count, and prothrombin time; and a lower arterial partial pressure of oxygen/fraction of inspired oxygen (PaO2 /FiO2 ). However, male sex, a low PaO2 /FiO2, and a high SOFA score were the only independent factors significantly associated with HFNC therapy failure. Conclusions: Male sex, a low PaO2 /FiO2, and a high SOFA score were independently associated with HFNC therapy failure in patients with severe COVID-19.